1999
DOI: 10.1038/sj.onc.1202275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of antizyme which targets the ornithine decarboxylase (ODC) required for cell growth and transformation

Abstract: Cell proliferation and transformation induced by growth factor stimulation or by carcinogens, viruses, or oncogenes are characterized by an associated increase in polyamine levels, which is mediated by increased polyamine biosynthesis and enhanced uptake of polyamines. Polyamine biosynthesis is catalyzed particularly, in the level of ornithine decarboxylase (ODC). The elevation of cellular polyamine levels on the other hand accelerates the induction of ornithine decarboxylase antizyme (antizyme), which is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 50 publications
1
61
0
2
Order By: Relevance
“…18 Growth induction of normal cells is known to be accompanied by a rapid transient increase in ODC activity. 33,34 Cell transformation induced by oncogenes such as v-src, neu, and ras has been shown to be associated with constitutively elevated ODC activity. 18,[35][36][37] The up-regulation of ODC is considered essential for cell transformation.…”
Section: Resultsmentioning
confidence: 99%
“…18 Growth induction of normal cells is known to be accompanied by a rapid transient increase in ODC activity. 33,34 Cell transformation induced by oncogenes such as v-src, neu, and ras has been shown to be associated with constitutively elevated ODC activity. 18,[35][36][37] The up-regulation of ODC is considered essential for cell transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Since elevated ODC activity is associated with most forms of human malignancies (Gerner and Meyskens, 2004), it was suggested early on that antizyme 1 may function as a tumor suppressor. Supporting this hypothesis, it has been shown that antizyme 1 overexpression leads to cell cycle arrest, apoptosis and reduced cell proliferation in vitro, (Iwata et al, 1999;Koike et al, 1999) and inhibits tumor growth in several mouse models in vivo (Iwata et al, 1999;Tsuji et al, 2001;Fong et al, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Higher levels of Az have been shown to be associated with decreased cell proliferation and hence Az has been considered as a tumor-suppressor (Iwata et al, 1999;Fong et al, 2003). It is tempting to speculate that the negative regulation of the oncogenic Aurora-A could be one of the manifestations of its tumor-suppressor functions.…”
Section: Antizyme1-dependent Aurora-a Degradation Sk Lim and G Gopalanmentioning
confidence: 99%
“…Increased polyamines and ODC activities are associated with many human malignancies (Gerner and Meyskens, 2004). As a negative regulator of ODC and thus polyamine levels, overexpression of Az leads to cell-cycle arrest, apoptosis (Iwata et al, 1999;Koike et al, 1999) and inhibition of tumor growth in in vivo mouse models (Feith et al, 2001;Fong et al, 2003). Az increases ODC degradation by enhancing ODC association with proteasome, rather than accelerating the rate of proteasomal processing (Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%